Mullerian Anomalies and Reproductive Performance among Infertile Women in Nepal (MedS Alliance Journal of Medicine and Medical Sciences, 2024)
Introduction: On average, one in five couples struggle with infertility, which is one of the biggest public health issues in the world. A congenital abnormality is too common for uterine abnormalities. Female children grow two distinct uteri during the time they develop inside the womb, which melds together before birth. Studying Mullerian abnormalities and reproductive performance in Nepalese infertile women was one of the study goals.Materials and Methods: A cross-sectional study design was used to evaluate Mullerian duct anomaly among infertile women. The study was conducted on infertile women who were receiving services from the infertility clinic of the Hospital for Advanced Medicine and Surgery [HAMS], Kathmandu, Nepal, during the year 2019–2020 AD. The study population included reproductive-aged women [aged 18–40 years] who had primary and secondary infertility. A hospital patient registry book was used to obtain the relevant information for the purpose of the study. An approval was obtained from the hosting hospital to proceed with the study. The "ASRM Mullerian Anomalies Classification 2021" was adopted for the classification of anomalies among women.Results: A total of 300 participants were included, among whom 61% [n = 183] had primary infertility and 39% [n = 117] had secondary infertility. The study revealed that 4.67% [n = 14] of pregnancies ended in miscarriage, 16.33% [n = 49] in preterm labor, 50.66% [n = 152] in normal spontaneous delivery [NSD], 27.67% [n = 83] in lower segment cesarean section [LSCS], and 0.7% [n = 2] in intrauterine fetal death [IUFD]. The current study attempted to identify the following methods of achieving pregnancy: spontaneous ovulation, 15% [n = 45]; ovulation induction, 54% [n = 162]; intrauterine insemination, 15% [n = 47]; IVF/ICSI, 14% [n = 42]; and not conceiving, 1.3% [n = 4].Conclusions: The present study showed that primary infertility affected 61% [n = 183] of participants, whereas secondary infertility affected 39% [n = 117]. A complete picture of Mullerian abnormalities cannot be drawn from the few studies available here; therefore, well-designed prospective studies are needed. Despite the fact that infertility has a medical basis, infertile women are nonetheless victims of all aspects of their social and personal lives in contemporary society in Nepal. To change the KAP among people in Nepal regarding infertility, BCC must be addressed.